HGG-55. An adolescent with a High-Grade Glioma: persuing a specific diagnosis. (3rd June 2022) - Luz, Inês Romão; Rebelo, Olinda; Costa, José Augusto; Carvalho, Alice
Abstract: BACKGROUND: Recognizing the value of molecular parameters provides evidence with repercussions on diseases classification. CLINICAL CASE: A thirteen-year-old girl was admitted in coma at the Intensive Care Unit due to a hemorrhagic stroke. CT revealed an expansive left frontal lobe lesion with perilesional edema and compression signs by an extensive hematoma. She underwent an emergency decompressive craniotomy for hematoma drainage, and the lesion was biopsied. The subsequent MRI showed a large heterogeneous mass with a cystic component. A first subtotal resection of the lesion was performed considering the language area. The histopathological examination showed tumor cells organized in perivascular pseudorosettes around the central hyalinized thickened blood vessel throughout the tumor, a pattern typically encountered in astroblastoma. Immunochemistry stains revealed a positive reactivity for GFAP, Olig2, and synaptophysin. The molecular study found a BRAFV600E mutation and homozygous CDKN2A e CDKN2B deletions; no TERT amplification, BCORL1, nor MN1 gene rearrangements were identified. She completed six weeks of radiotherapy without neurological signs/symptoms. A new surgical intervention was done 12 weeks later due to a slight increase of residual lesion. The rapid growth and the presence of viable tumor cells justified the therapy with irinotecan and bevacizumab, with mild adverse effects. One year after diagnosis, the adolescent is clinically well, without neurologic deficits and the MRI without evidence of residue or tumor recurrence. DISCUSSION: We began therapy based on morphological diagnosis. Complete resection and radiotherapy proved to be beneficial as in other high-grade gliomas, but the value of other therapies is still unknown. The BRAF gene variant would allow treatment with dabrafenib (in association with trametinib) or vemurafenib; however, she presents molecular findings associated with poor prognosis (CDKN2A deletion) that may impair the effectiveness of these therapies. According to the new WHO classification, the absence of MN1 alterations precludes the diagnosis of astroblastoma.